Bird Diversity as a Support of Ecotourism Activities in the Mangrove Ecosystem of Lembongan Island Bali - GINANTRA, I Ketut; MUKSIN, I Ketut; JONI, Martin; YUNI, Luh Putu Eswaryanti Kusuma (Journal of Environmental Management and Tourism, 2022)
Research has been carried out on bird diversity to support ecotourism attractions in the mangrove area of Lembongan Island. The research was conducted in April - August 2021. The focus of this research is the identification, description of bird species and the use of habitats for bird activities. To achieve this goal, the following steps were taken: Identification of bird species based on morphological characteristics, determining the abundance of bird species using the point count method, determining bird activity at each ecosystem site of mangroves with ad libitum sampling method. Bird species diversity was determined by the Shannon-Wiener index. The results of the study found 32 species of birds belonging to 26 families. Most of the birds found were terrestrial birds with 21 species, and water birds (shore birds) with 11 species. Overall, the diversity of bird species in the mangrove ecosystem is in the high category (diversity index 3.03) and the species evenness index is high (evenness index 0.87). The types of vegetation used by birds at the 7 research sites were mangrove vegetation, mangrove associations and dry land vegetation. The presence of birds, bird conservation status, bird activities, habitat use by birds in mangrove habitats are attractive attractions for ecotourism.